The Yale-Brown Obsessive-Compulsive Scale: Factor Structure of a Large Sample - Anholt, Gideon; Oppen, Patricia v.; Cath, Danielle; Smit, Jan; Den Boer, Johan A.; Verbraak, Marc J.; Van Balkom, Anton J. (Frontiers in Psychiatry, 2010)
The Yale Brown Obsessive-Compulsive scale (Y-BOCS) is a semi-structured interview considered to be the gold standard in the measurement of obsessive-compulsive disorder (OCD) severity, yet findings about its factorial structure are conflicting. This study aimed at comparing different models, and testing whether factorial structure differs along various sub-groups. Exploratory and confirmatory factor analyses were conducted on Y-BOCS scores of a large OCD patient group (n=544). A three factor structure (obsessions, compulsions, and resistance) provided the best fit for the data across different factor analytic procedures. The difference in goodness of fit between the original two factor (obsessions and compulsions) and the three factor solutions seemed, however, very small. Since the two factor solution is the original theory-driven structure, and the most widely used, we recommend the use of this factor.